Delicate Years: Children and Identity in Zimbabwean Literature - Muganiwa, Josephine (Commonwealth Youth and Development, 2018)
The paper argues that children face challenges in growing up and fitting into their societies and that these challenges need to be addressed with care. These challenges, which are complicated by the effects of colonialism, war and economic crises in the context of Zimbabwe, are portrayed in the novels Nervous Conditions (Dangarembga 1989), The Book of Not (Dangarembga 2006), The Uncertainty of Hope (Tagwira 2006) and Running with Mother (Mlalazi 2012). In analysing the characters of the children portrayed in these four novels, the vulnerability of children, regardless of their age, is demonstrated. The child characters strive to help their parents and be useful citizens and yet at times this contrasts with their desire to be sheltered and treated as children. This contradiction is best exhibited in teenagers who try to fashion their own identity that is separate from the people around them but who still require guidance to do so.